Sustainable development of suppliers – a systematic review of the literature - Jedynak, Monika; Kuźniarska, Aneta; Mania, Karolina (Contemporary organisation and management. Challenges and trends, 2020)
The purpose of the article was to conduct a systematic analysis of reviewed scientific publications covering the subject of sustainable development of suppliers. Bibliometric and contextual analysis allowed the formulation of the following conclusions: 1) the issue of sustainable development of suppliers is present in peer-reviewed scientific publications to a very moderate level, 2) the small number of publications does not make it possible to determine whether there is a trend in terms of publication time, 3) scientific journals in which articles on sustainable development of suppliers were published have a different profile, 4) authors who undertake the issues analyzed come from different countries, 5) sustainable development of suppliers is the subject of research in a range of research areas. Following a systematic review of the literature, proposals for future research directions were also formulated.